Biological pretreatment and fermentation of Panicum antidotale biomass for pectinase production by Bacillus vallismortis - Amal Siraj; Uroosa Ejaz; Masooma Hassan; Mohammed Alorabi; Abdullah K. Alanazi; Muhammad Sohail (PLoS ONE, 2026)
Halophytic plants are renewable source of lignocellulosic biomass, however, are underexplored for their utilization as a source of fermentation raw material. Similar to glycophytes, biomass from halophytes contains lignin that is removed to provide access to the fermentable carbohydrates. This study was designed to investigate biomass of a halophytic plant, Panicum antidotale, for pectinase production from a halotolerant strain of Bacillus vallismortis MH 10. Laccase from a fungus, Trametes pubescens MB 89 was employed as a pretreatment agent to remove lignin. The pectin content of P. antidotale biomass was also determined and compared with the pectin extracted from orange peels (OP). The changes in the P. antidotale biomass and pectin were investigated using Fourier Transform Infrared spectroscopy (FTIR) and Scanning Electron microscope (SEM). The strain MH 10 produced 17.39 IU mL -1 pectinase in the medium containing P. antidotale biomass supplemented with fungal laccase. The data showed that P. antidotale biomass has a meagre quantity of pectin (2.8%) compared to OP (14.9%). Yet the strain MH 10 produced 315 IU g -1 pectinase by fermenting pectin from P. antidotale but only 76.32 IU g -1 pectinase was obtained by using OP as substrate which showed preference of this strain towards halophytic substrate. The analysis further revealed that the strain effectively utilized 94% pectin content of P. antidotale biomass. The FTIR spectra corresponded to the changes in pectin spectrum indicating pectin consumption from P. antidotale biomass. The SEM images confirmed the laccase-mediated porosity and fragility in the biomass. Hence, this study provides a novel utilization of biomass from halophytes as a chemical feedstock.